Determining Factors of Compliance in Paying Land and Building Tax - DICRIYANI, Ni Luh Gede Mahayu; DEWI, Ni Luh Putu Sandrya; ARSANA, I Made Marsa (PT Keberlanjutan Strategis Indonesia, 2025)
Compliance level in PBB payments can be influenced based on a study from the Theory of Planned Behavior (TPB), compliance pay, Tax Land and Buildings of the United Nations, influenced by a number of main factors that are tax knowledge, fiscal awareness, firmness of sanctions and enforcement, as well as economic conditions. Objective study This For testing tax knowledge, fiscal awareness, firmness of sanctions and enforcement, as well as economic conditions for compliance in paying PBB. Implementation study. This was done on a mandatory basis in Taxes in Tabanan Regency. The research location determined by researchers due to Tabanan Regency has level low PBB compliance level. Retrieval sample done with the Purposive sampling technique. Research results show that hypothesis test results show that hypothesis third, that is, firmness sanctions and enforcement have no influence on compliance with paying the rejected PBB. The first, second and fourth hypotheses are accepted, namely, Tax knowledge has a positive effect on compliance in paying PBB, fiscal awareness has a positive influence on compliance in paying PBB and economic conditions have a positive influence on compliance in paying PBB.